PENGARUH TRANSAKSI E-COMMERCE DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF MAHASISWA - Sri Mulyati (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
Overconsumption of goods and services is a tendency that is now on the rise, particularly among students. Students also exhibit the traits of a generation that is growing more and more resistant to technology development, especially online shopping. Any objective of this study is to analyze E-commerce transactions and lifestyle choices in relation to consumer demand by using a quantitative survey method. Research data was collected through a questionnaire, the research respondents were FKIP level IV undergraduate students at Kuningan University for the 2021/2022 academic year which consisted of six (6) study programs. The population in this study amounted to 279 and a sample of 164 students was drawn. Analysis of research data using multiple regression and prerequisite analysis of normality, multicollinearity and linearity of the data. The results of the study revealed that Shopee E-commerce transactions, lifestyle and consumptive behavior of students ranged from moderate criteria. The results of hypothesis testing show that E-commerce transactions and lifestyle affect the level of consumptive behavior. As students who live side by side with rapid technological developments, students should have self-awareness and behave more rationally